ANALISIS KANDUNGAN INFORMASI LAPORAN ARUS KAS DI BURSA EFEK JAKARTA - Sri Wahyuni (Journal of Indonesian Economy and Business (JIEB), 2002)
The purpose of this study is to examine the information content of total cash flows. As much as 88 manufacturing firm listed in The Jakarta Stock Exchange (JSE) were taken as sample using a purposive sampling method. The statistics method used to test hypotheses is a linear regression in the return model. The results of this study shows that : 1). Information content in cash flows statement the condition of good news is not significantly associated with the stock return increase around the financial statement publication date. 2). Information content in cash flows statement the condition of bad news is not significantly associated with the stock return decrease around the financial statement publication date.Keywords : Cash flows, information content, return model, stock return.